1994
DOI: 10.1111/j.1432-1033.1994.tb18790.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and molecular cloning of mannose‐binding lectins from the Orchidaceae species Listera ovata, Epipactis helleborine and Cymbidium hybrid

Abstract: Mannose-binding lectins were purified from the leaves of three Orchidaceae species, namely Listera ovata (twayblade), Epipactis helleborine (broad-leaved helleborine) and Cymbidium hybrid, using affinity chromatography on mannose-Sepharose-4B. Apparently, the Orchidaceae lectins are dimeric proteins composed of lectin subunits of 12-13 kDa. All of the isolated lectins exhibit exclusive specificity towards mannose.A cDNA library constructed from poly(A) rich RNA isolated from leaves of L. ovata was screened for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…The Man-binding lectins (and lectin genes) from the plant families Amaryllidaceae, Alliaceae, and Orchidaceae have in particular been intensively studied, since they represent a superfamily of evolutionary well-conserved proteins with unique biological, physiological, and molecular biological properties (Van Damme et al, 1991b, 1992a, 1992b, 1993a, 1993b, 1994a, 1994b. Moreover, the finding that several members of this lectin family exhibited insecticidal activity in feeding experiments with both artificial diets and transgenic plants (Powell et al, 1993;Gatehouse et al, 1995) not only suggested that they are involved in the plant's defense but also demonstrated their potential use in crop protection against phytophagous invertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Man-binding lectins (and lectin genes) from the plant families Amaryllidaceae, Alliaceae, and Orchidaceae have in particular been intensively studied, since they represent a superfamily of evolutionary well-conserved proteins with unique biological, physiological, and molecular biological properties (Van Damme et al, 1991b, 1992a, 1992b, 1993a, 1993b, 1994a, 1994b. Moreover, the finding that several members of this lectin family exhibited insecticidal activity in feeding experiments with both artificial diets and transgenic plants (Powell et al, 1993;Gatehouse et al, 1995) not only suggested that they are involved in the plant's defense but also demonstrated their potential use in crop protection against phytophagous invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization and molecular cloning of the Man-binding lectins from several Amaryllidaceae, Alliaceae, and Orchidaceae species demonstrated that they a11 belong to one large superfamily of Man-binding proteins that show a considerable overall sequence homology within the mature protein and, in addition, contain highly conserved domains (Van Damme et al, 1991b, 1992a, 199213, 1993a, 1993b, 1994a, 1994b. In search of possible new members of the Man-binding monocot lectins our attention was drawn to a previously isolated but yet uncharacterized agglutinin Plant Physiol.…”
mentioning
confidence: 99%
“…The best-characterized lectins are those isolated from the seeds of leguminous plants [1]. Lectins have also been purified from leaves [2~], roots [5,6] and bulbs [7][8][9], and cDNAs that encode such lectins have been cloned [4,10,11]. The bark of woody plants is also a source of lectins [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence alignment of LECrxL-MI1 and previously cloned monocot mannose-binding lectins from Amaryllidaceae, Alliaceae and Orchidaceae revealed 39- (Van Damme et al, 1991), the Orchidaceae species Listeru ovuta (LECLOA1 and LECLOA2) (Van Damme et al, 1994), the Alliaceae species Allium sativum (ASAIdoml, ASAIdom2 and LECASAII) (Van Damme et al, 1992b), Alliurn ascalorzicurn (LECAAA) (Van Damme et al, 1993a), Alliurn cepa (LECACA) (Van Damme et al, 1993a), Alliurn porrum (LECAPA) (Van Damme et al, 1993a) and Alliurn ursinum (LECAUAGI and LECAUAG2) (Van Damme et al, 1993b), and the Araceae species Arum muculuturn (AMAldoml and AMAldom2) (Van Damme et al, 1995 b).…”
Section: Lect>rlci2: -----A------------------t----s----------------mentioning
confidence: 99%
“…bark, bulbs, tubers, rhizomes and corms are particularly rich sources of lectins . Although representatives of most taxonomic groupings contain lectins in some vegetative tissue, the research on non-seed lectins has been focused on leaf, stem and root lectins of a few legume species (Etzler, 1994), bark lectins of a few trees (Nsimba-Lubaki and Peumans, 1986;Hankins et al, 1988;Yoshida et al, 1994;Van Damme et al, 199Sa) and on the bulb and tuberkorm lectins of a limited number of representatives of the monocot families Amaryllidaceae (Van Damme et al, 1987), Alliaceae (Van Damme et al, 1992b, 1993a, Orchidaceae (Van Damme et al, 1994), Araceae (Van Damme et al, 1995b) and, to a lesser extent, Liliaceae (Oda and Minami, 1986;Cammue et al, 1986;Oda et al, 1987;Koike et al, 1995). Surprisingly, all the lectins found thus far in storage organs of Amaryllidaceae, Alliaceae, Orchidaceae and Araceae species belong to a single superfamily Enzyme.…”
mentioning
confidence: 99%